Pilot-scale evaluation of native plant–based constructed wetland performance in a cold climate - Adrian L. D. Paul; Alexandre Licinio; Marie-Christine Simard; Roberta D’Camp; Michel Labrecque (Environmental Science and Pollution Research, 2026)

Efficiency of planted and unplanted vertical flow aerated filters in treatment of young landfill leachate - Elizabeth Shively; Seyedmortaza Mortazavi; Rosalie Boutin; Marie-Pierre Bastien-Thibault; Timea Török; Daphné Gagnon-Fee; Sanaz Alizadeh; Margit Kõiv-Vainik; Jalal Hawari; Michel Labrecque; Yves Comeau (Ecological Engineering, 2025)

Willow traits outperform taxonomy in predicting phytoremediation services - Béatrice Gervais-Bergeron; Pierre-Luc Chagnon; Michel Labrecque (Science of The Total Environment, 2024)

A comprehensive review of planting approaches used to establish willow for environmental applications - Kankan Shang; Michel Labrecque; Vincent Gilles; Werther Guidi Nissim (Ecological Engineering, 2024)

Trace element translocation patterns in the epigeous parts of 15 common Canadian urban plant species grown in a contaminated soil - Esther Lapierre; Cédric Frenette-Dussault; Frédéric E. Pitre; Michel Labrecque; Werther Guidi Nissim (Plant Biosystems, 2024)

Assessment of different procedures for in vitro propagation of Salix miyabeana - Werther Guidi Nissim; Gabrielle Corte Fadel; Michel Labrecque (Plant Biosystems, 2024)

Conversion of CO2 by reverse water gas shift (RWGS) reaction using a hydrogen oxyflame - Ali Shekari; Raynald Labrecque; Germain Larocque; Michel Vienneau; Martin Simoneau; Robert Schulz (Fuel, 2023)

Trace element hyperaccumulator plant traits: a call for trait data collection - Béatrice Gervais-Bergeron; Adrian L. D. Paul; Pierre-Luc Chagnon; Alan J. M. Baker; Antony van der Ent; Michel-Pierre Faucon; Celestino Quintela-Sabarís; Michel Labrecque (Plant and Soil, 2023)

Photosynthetic patterns during autumn in three different Salix cultivars grown on a brownfield site - Emily Palm; Werther Guidi Nissim; Daphné Gagnon-Fee; Michel Labrecque (Photosynthesis Research, 2022)
Leaf senescence at the end of the growing season is a complex process stimulated by changes in daylength and temperature that prepares deciduous trees for winter by reducing photosynthetic rates and remobilization of nutrients. Extending the duration of photosynthetic activity could have important consequences for the translocation of heavy metals in the phytoremediation of contaminated sites using deciduous trees like willow. In the present study, three Salix cultivars (‘India,’ ‘SX67,’ and ‘Fish Creek’) that were observed to maintain green leaves late into autumn were evaluated over an 11-week period extending from mid-September to mid-November on a brownfield site in Montreal, Canada. Gas exchange rates, chlorophyll fluorescence, and leaf pigments were measured weekly. A general trend of declining stomatal conductance and transpiration were observed early in the trial, followed by reductions in photosynthetic efficiency and concentrations of chl a, chl b, and carotenoids, in agreement with other studies. In particular, the cultivar ‘Fish Creek’ had higher rates of gas exchange and pigment concentrations than either ‘SX67’ or ‘India,’ but values for these parameters also declined more rapidly over the course of the trial. Both photoperiod and soil and air temperatures were strong drivers of changes in photosynthetic activity in all three of these cultivars according to correlation analyses. Further studies should focus on their biomass production and heavy metal accumulation capacity in light of the observed variation in photosynthetic activity stimulated by seasonal changes in light and temperature.

Root System Architecture of Salix miyabeana “SX67” and Relationships with Aboveground Biomass Yields - Mario Fontana; Alexandre Collin; François Courchesne; Michel Labrecque; Nicolas Bélanger (BioEnergy Research, 2020)

Quantifying the effects of soil and climate on aboveground biomass production of Salix miyabeana SX67 in Quebec - Mario Fontana; Michel Labrecque; Christian Messier; François Courchesne; Nicolas Bélanger (New Forests, 2017)

First-Rotation Performance of Five Short-Rotation Willow Cultivars on Different Soil Types and Along a Large Climate Gradient - Benoit Lafleur; Olivier Lalonde; Michel Labrecque (BioEnergy Research, 2017)

Maximum Annual Potential Yields of Salix miyabeana SX67 in Southern Quebec and Effects of Coppicing and Stool Age - Mario Fontana; Benoit Lafleur; Michel Labrecque; François Courchesne; Nicolas Bélanger (BioEnergy Research, 2016)

Genotypic differences explain most of the response of willow cultivars to petroleum-contaminated soil - Vanessa Grenier; Frédéric E. Pitre; Werther Guidi Nissim; Michel Labrecque (Trees, 2015)

Willow Root Development and Morphology Changes Under Different Irrigation and Fertilization Regimes in a Vegetation Filter - Ahmed Jerbi; Werther Guidi Nissim; Rémy Fluet; Michel Labrecque (BioEnergy Research, 2015)

Soil carbon sequestration potential of willows in short-rotation coppice established on abandoned farm lands - Jérémie Lockwell; Werther Guidi; Michel Labrecque (Plant and Soil, 2012)

Phytoextraction of heavy metals by two Salicaceae clones in symbiosis with arbuscular mycorrhizal fungi during the second year of a field trial - Laurence Bissonnette; Marc St-Arnaud; Michel Labrecque (Plant and Soil, 2010)

Effects of High Water Supply on Growth, Water Use, and Nutrient Allocation in Willow and Poplar Grown in a 1-Year Pot Trial - Werther Guidi; Michel Labrecque (Water, Air, & Soil Pollution, 2010)

Potentially pathogenic and biocontrol Ascomycota associated with green wall structures of basket willow (Salix viminalis L.) revealed by phenotypic characters and ITS phylogeny - Vladimir Vujanovic; Michel Labrecque (BioControl, 2008)

Phytoremediation of heavy metal and PAH-contaminated brownfield sites - Sébastien Roy; Suzanne Labelle; Punita Mehta; Anca Mihoc; Nathalie Fortin; Claude Masson; René Leblanc; Guy Châteauneuf; Christine Sura; Christine Gallipeau; Caroline Olsen; Serge Delisle; et al. (Plant and Soil, 2005)